Video conferencing in court proceedings by European Union legislation legal regulation - Ozernyuk, Ganna (ScienceRise: Juridical Science, 2020)
The scientific article is devoted to the videoconferencing in court proceedings by international law and the law of some European Union countries. The videoconferencing definition, the right to justice protection on the main international legal sources about the trial regulation and human rights to justice protection bases are studied, the procedural stages of court hearings by videoconference are analyzed. Carrying out comparative legal research at our country present stage legal transformation and development, especially related to the emergence of new, modern legal relations, is primarily due to the need to receive international and foreign experience and, consequently, improve current national legislation. It has been established, that the latest technologies introduction in the judicial process at the national and international levels has both advantages and disadvantages and is closely related to the protection and implementation of the right to justice. Normative legal acts about the right to justice consolidation are primary regarding the right of participants in court proceedings to participate in it by videoconference. The attractive side of conducting court hearings online includes: the availability of litigation for all participants, regardless of their location, saving time and money, compliance with legal requirements for the duration of litigation, and so on. Despite the general legal consolidation of the possibility of holding videoconferences in Ukraine and the EU, the procedural features of the rights and obligations of participants in such proceedings remain unclear, as well as unspecified issues regarding the application of different types of technical equipment depending on the conditions of video calls, the possibility of holding meetings outside the court in emergency conditions, etc.